2009
DOI: 10.1103/physrevb.79.165101
|View full text |Cite
|
Sign up to set email alerts
|

Density functional theory study of Fe(II) adsorption and oxidation on goethite surfaces

Abstract: We study the interactions between Fe(II) aqua-complexes and surfaces of goethite (α-FeOOH) by means of density-functional theory calculations including the so-called Hubbard U correction to the exchange-correlation functional. Using a thermodynamic approach, we find that (110) and (021) surfaces in contact with aqueous solutions are almost equally stable, despite the evident needle-like shape of goethite crystals indicating substantially different reactivity of the two faces. We thus suggest that crystal aniso… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
70
3

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(86 citation statements)
references
References 56 publications
13
70
3
Order By: Relevance
“…In this way we found that for both functionals the most stable magnetic phase was that of the AFM arrangement, which corresponds to the situation where each Fe atom is surrounded by other two Fe atoms with opposite magnetic moments along the b-vector axis. These results are in agreement with experiments [2] and with previous calculations reported by other authors using the functional form of Perdew, Burke and Enzerhof (PBE) [32].…”
Section: Bulk Goethitesupporting
confidence: 95%
See 1 more Smart Citation
“…In this way we found that for both functionals the most stable magnetic phase was that of the AFM arrangement, which corresponds to the situation where each Fe atom is surrounded by other two Fe atoms with opposite magnetic moments along the b-vector axis. These results are in agreement with experiments [2] and with previous calculations reported by other authors using the functional form of Perdew, Burke and Enzerhof (PBE) [32].…”
Section: Bulk Goethitesupporting
confidence: 95%
“…Introducing a non zero U eff , the bulk modulus increase with a lineal trend between the experimental data. A recent theoretical work of goethite using PBE functional and ultrasoft pseudopotentials showed that the bulk modulus value obtained with GGA þ U (U eff ¼ 5.2 eV) reproduced the lower experimental value [32], but all the cell parameters were higher than our results.…”
Section: Bulk Goethitecontrasting
confidence: 48%
“…The energy separation between P 1 and P 2 is found to be about 1.5 eV, both in experimental and calculated spectra. This value is consistent with (i) ground state DOS calculations performed in pure goethite by Otte et al (2009) and Russell et al (2009), and (ii) the O K-edge XANES spectrum of bulk goethite recorded by Gilbert et al (2007). In addition, the P 1 -P 2 energy difference may provide an estimate of the ∆ 0 crystal field parameter (in O h symmetry), which is defined as the energy difference between the single-electron configurations t 2g 0 e g 1 and t 2g 1 e g 0 (König and Kremer, 1977).…”
Section: Pre-edge Analysissupporting
confidence: 76%
“…We use a slightly modified version of the summation as explained in Appendix C. Up to this point we did not specify the form of the localized basis |χ mR and the formalism remained general. In CASTEP, we use an already implemented LCAO basis, with the radial part derived from pseudopotential [28], which can be either norm-conserving or ultrasoft. In the case of norm-conserving pseudopotentials, the states |χ mR are orthogonal by construction, while in the case of ultrasoft ones [29] these states are overlapping with an overlap matrix S:…”
Section: A General Formalismmentioning
confidence: 99%